Implementation of Search Engine Optimization Techniques In Increasing Traffic of the Bima Utomo Waterpark Website - Tantri Hidayati Sinaga; Edrian Hadinata (Jurnal Komputer Terapan, 2019)
Today's business people have generally used information technology for business activities, one of which is the use of a website as a medium to facilitate the promotion of business activities to a wider market. There are many ways that business people can use to promote the website pages they have for potential customers, the common methods used include using email blast, advertising using third party services, the use of social network media and media blog. One very effective way is to utilize search engine optimization techniques, this is because internet users often search for information through search engines like Google. Search Engine Optimization (SEO) is a series of processes carried out systematically and aims to increase the volume and quality of traffic visited by search engines to certain websites by utilizing the search engine algorithm, which is called PageRank. The purpose of SEO is to place a website on the top position of search results based on certain keywords targeted. This research will apply SEO techniques to increase the number of visitors to the Bima Utomo Waterpark website through the Google search engine. The results of this study are expected to increase the popularity of the Bima Utomo Waterpark website.